18F‐RB390: Innovative ligand for imaging the T877A androgen receptor mutant in prostate cancer via positron emission tomography (PET). Issue 4 (30th October 2014) - Bertolini, Reto; Goepfert, Christine; Andrieu, Thomas; Nichols, Sara; Walter, Martin A.; Frey, Felix J.; McCammon, J. Andrew; Frey, Brigitte M.
<x xml:space="preserve">Abstract</x> BACKGROUND Detecting prostate cancer before spreading or predicting a favorable therapy are challenging issues for impacting patient's survival. Presently, 2‐[18F]‐fluoro‐2‐deoxy‐D‐glucose (18F‐FDG) and/or 18F‐fluorocholine (18F‐FCH) are the generally used PET‐tracers in oncology yet do not emphasize the T877A androgen receptor (AR) mutation being exclusively present in cancerous tissue and escaping androgen deprivation treatment. METHODS We designed and synthesized fluorinated 5α‐dihydrotestosterone (DHT) derivatives to target T877A‐AR. We performed binding assays to select suitable candidates using COS‐7 cells transfected with wild‐type or T877A AR (WT‐AR, T877A‐AR) expressing plasmids and investigated cellular uptake of candidate 18F‐RB390. Stability, biodistribution analyses and PET‐Imaging were assessed by injecting 18F‐RB390 (10MBq), with and without co‐injection of an excess of unlabeled DHT in C4‐2 and PC‐3 tumor bearing male SCID mice (n = 12). RESULTS RB390 presented a higher relative binding affinity (RBA) (28.1%, IC50 = 32 nM) for T877A‐AR than for WT‐AR (1.7%, IC50 = 357 nM) related to DHT (RBA = 100%). A small fraction of 18F‐RB390 was metabolized when incubated with murine liver homogenate or human blood for 3 hr. The metabolite of RB390, 3‐hydroxysteroid RB448, presented similar binding characteristics as RB390. 18F‐RB390 but not 18F‐FDG or 18F‐FCH accumulated 2.5× more in COS‐7 cells transfected with pSG5AR‐T877A than with control plasmid. Accumulation was reduced with an excess of DHT. PET/CT imaging and biodistribution studies revealed a significantly higher uptake of 18F‐RB390 in T877A mutation positive xenografts compared to PC‐3 control tumors. This effect was blunted with DHT. CONCLUSION Given the differential binding capacity and the favorable radioactivity pattern, 18F‐RB390 represents the portrayal of the first imaging ligand with predictive potential for mutant T877A‐AR in prostate cancer for guiding therapy. Prostate 75:348–359, 2015. © 2014 Wiley Periodicals, Inc.